2018
DOI: 10.3390/w10030337
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Permeable Pavement Clogging Investigations and Recommended Maintenance Regimes

Abstract: Understanding clogging mechanisms in permeable pavements can help optimize the required maintenance regime. In this review paper, methods for investigating clogging mechanisms are described. These include surface infiltration methods, the use of embedded sensors, and the development of modelling tools. Previously conducted surface infiltration tests indicate the importance of the age of a permeable pavement system and also local climatic conditions, including rainfall intensity. The results indicate that porou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Few studies also have discussed the material's effects on the efficiency of permeable pavements in controlling runoff quantity and quality at the small scale [23]. In real world applications, clogging of the pavement system is one the serious issue which needs to be investigated further for coming years [24]. In this way, we can develop a sustainable design for permeable pavements that can solve urban water related problems in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies also have discussed the material's effects on the efficiency of permeable pavements in controlling runoff quantity and quality at the small scale [23]. In real world applications, clogging of the pavement system is one the serious issue which needs to be investigated further for coming years [24]. In this way, we can develop a sustainable design for permeable pavements that can solve urban water related problems in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In current Chinese technical specification, the crushing value of the coarse aggregate for surface layer of asphalt pavement is no greater than 26% [1]. So, the crushing value standard of basalt coarse aggregate used in PA mixture should be increased to not more than 26%/1.48 � 17.6%.…”
Section: Recommended Crushing Value Standard Of Coarse Aggregate In Pmentioning
confidence: 97%
“…e crushing of coarse aggregate in PA mixture is caused by the excessive contact pressure between aggregates, so the coarse aggregates are more easily crushed by vehicle load. So, the crushing value of coarse aggregate is very important for the durability of PA mixture [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…One interesting study observed the influence of drainage area and rainfall (1 mm clogging for each 6 mm of rainfall depth) on the progression of surface clogging [33]. A previously developed regression model from a laboratory investigation was able to assess physical clogging in permeable pavements, which estimated the clogging activity as a function of runoff volume and flow rate [34,35]. Another study developed an artificial neural network for prediction clogging, which concluded that certain factors, such as peak rainfall intensities over 5 min, and both previous and cumulative rainfall magnitude, are highly influential in forecasting the hydrologic performance of permeable pavements [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…A previously developed regression model from a laboratory investigation was able to assess physical clogging in permeable pavements, which estimated the clogging activity as a function of runoff volume and flow rate [34,35]. Another study developed an artificial neural network for prediction clogging, which concluded that certain factors, such as peak rainfall intensities over 5 min, and both previous and cumulative rainfall magnitude, are highly influential in forecasting the hydrologic performance of permeable pavements [35,36]. However, most models are not complete enough to factor in the complexities of maintenance activities, such as street sweeping or vacuuming, on the performance of permeable pavements [37].…”
Section: Introductionmentioning
confidence: 99%